TREATMENT OF TUBERCULOSIS PATIENTS WITH EXTENSIVE DRUG RESISTANCE USING NEW ANTI-TUBERCULOSIS DRUGS IN THE CIVILIAN COMMUNITY OF ARKHANGELSK REGION - GАYDА, А. I.; SVESHNIKOVА, O. M.; VERKHOVАYA, V. N.; MАKHMАEVА, S. V.; NIKISHOVА, E. I.; MАRYANDYSHEV, А. O. (Tuberkulëz i bolezni lëgkikh, 2018)
The objective: to assess treatment outcomes in tuberculosis patients with extensive drug resistance (XDR TB) treated by new anti-tuberculosis drugs in the civilian community of Arkhangelsk Region.The analysis included all cases of XDR TB registered in the civilian community of Arkhangelsk Region from November 2006 to December 2013; treatment outcomes were assessed in 21 patients who were treated by regimens containing new anti-tuberculosis drugs (bedaquiline, delamanid, linezolid, clofazimine, imipenem with amoxiclav). 16 patients were treated by regimens containing 4 new anti-tuberculosis drugs. 2 patients were treated by regimen IV containing two drugs – bedaquiline, linezolid and bedaquiline, clofazimine; and 3 patients with regimens containing bedaquiline only.From November 2006 to December 2017, 175 XDR TB patients were registered in Arkhangelsk Region. The effective chemotherapy using new drugs made 57%, and mortality made 4.7%. In-take of new anti-tuberculosis drugs was accompanied side effects of minor and moderate degree.New anti-tuberculosis drugs are to be studied further in order to work out the most effective regimens for treatment of XDR TB patients.